UNEMPLOYMENT IN JAMMU AND KASHMIR: A SOCIAL RESEARCH STUDY - Mohd Arif Naikoo (Journal of International Islamic Law, Human Right and Public Policy, 2023)
This research paper examines the issue of unemployment in Jammu and Kashmir, a region marked by political instability and economic challenges. The study aims to identify the causes, impacts, and potential solutions to the unemployment crisis. By employing both qualitative and quantitative research methods, this paper provides a comprehensive analysis of the current employment landscape, factors contributing to high unemployment rates, and the social and economic repercussions of joblessness in the region. Policy recommendations are also discussed to address the underlying issues and promote sustainable economic growth.